(Re)Writing Communities and Identities - Marzluf, Phillip; Goins, Anna; Debes, Cindy; Gray, Stacia; Knoblauch, A. Abby (Open textbook library., 2024)
(Re)Writing Communities and Identities enables college-level students to develop their ability to compose various informative and expressive genres, including analyses, reflections, summaries, syntheses, and informative reports. While students raise their consciousness about their writing process and audience-based informative strategies, they also familiarize themselves with important social and cultural issues related to the theme of "identities and communities."